High-toughness polylactic acid composite material and preparation method thereof

By introducing a compatibilizer into the polylactic acid material and M-SR produced by polymerization reaction, the stable network structure is formed, which solves the problem of insufficient toughness of the polylactic acid material and significantly improves its application potential in high-demand fields.

CN119823549APending Publication Date: 2025-04-15HUIZHOU XINCHANGLONG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510053085.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Polylactic acid materials themselves have the disadvantages of poor flexibility of molecular chains, low toughness, easy to break when deformation, and slow crystallization speed, which limits their application in certain fields with high requirements for material toughness.

Method used

The toughness of the polylactic acid composite material is significantly improved by introducing compatibilizers and M-SR. M-SR is prepared by polymerization reaction of toughening agents, reactive monomers, crosslinking agents and antioxidants, and forms a stable network structure with polylactic acid through copolymerization reaction to improve the overall performance of the material.

Benefits of technology

It significantly improves the toughness and mechanical properties of polylactic acid composite materials, making them suitable for areas such as 3D printing, automobiles, and electronics that require high material toughness, while improving the processing performance and production efficiency of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240552690000121
    Figure BDA0005240552690000121
  • Figure HDA0005240552700000011
    Figure HDA0005240552700000011
  • Figure HDA0005240552700000012
    Figure HDA0005240552700000012
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and particularly discloses a high-toughness polylactic acid composite material and a preparation method thereof. The high-toughness polylactic acid composite material is prepared from the following raw materials in parts by weight: 100 parts of polylactic acid, 5-20 parts of a compatilizer and 5-30 parts of M-SR, wherein the M-SR is prepared from a toughening agent, a reaction monomer, a cross-linking agent and an antioxidant through a polymerization reaction. The polylactic acid composite material disclosed by the invention has relatively high toughness while maintaining the excellent performance of the polylactic acid material, the highest notch impact strength of the polylactic acid composite material can reach 37.28 KJ / m < 2 >, the product quality is relatively high, and the polylactic acid composite material can be widely applied to the fields of 3D printing, automobiles, electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer materials, and more specifically, to a high-toughness polylactic acid composite material and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA), as a completely biodegradable green polymer material, has been widely used in the field of 3D printing in recent years. It has become an important role in 3D printing consumables due to its advantages such as non-toxicity, no irritating odor, high mechanical strength, low melting temperature, small cooling shrinkage, transparency and easy dyeing, and good processing performance. However, PLA material itself has disadvantages such as poor molecular chain flexibility, low toughness, easy brittle fracture during deformation, and slow crystallization speed, which limits its application in some fields that require high material toughness.

[0003] At present, there are many methods for toughening and modifying PLA to improve its comprehensive performance. For example, the Chinese patent with the announcement number CN111890650A, which obtains toughened PLA material by melt blending polyurethane (TPU) material with PLA material, but due to the problem of compatibility between the two, the toughening effect of this method is not stable. For example, the Chinese patent with the announcement number CN106221152A, which solves the problem of poor toughness of PLA and poor fluency in the printing process by adding silane coupling agent, but its preparation method is relatively complicated, and the final effect is not ideal. Therefore, in view of the problem of poor toughness of PLA material and the defects of the prior art, it is of great significance to develop a high-toughness polylactic acid composite material. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a high-toughness polylactic acid composite material and a preparation method thereof, aiming to make the PLA material have higher toughness, so that it can be more widely used in fields such as 3D printing, automobiles, electronics, etc. that have high requirements on material toughness.

[0005] In the first aspect, the present application provides a high-toughness polylactic acid composite material, which adopts the following technical solution: A high-toughness polylactic acid composite material, the raw materials used include the following components: 100 parts by weight of polylactic acid; Compatibilizer 5-20 parts by weight; M-SR 5-30 parts by weight; The M-SR is prepared by polymerization of a toughening agent, a reactive monomer, a crosslinking agent and an antioxidant.

[0006] Preferably, the M-SR is prepared by the following method: 10-20 parts by weight of toughening agent, 0-20 parts by weight of reactive monomer, 1-5 parts by weight of cross-linking agent and 0.1-0.5 parts by weight of antioxidant are mixed, and the mixture is reacted at a temperature of 75-85°C and a pressure of 10-20 MPa for 6-12 hours. After the reaction is completed, the mixture is allowed to stand for 3-6 hours, and then mixed and stirred with ethanol at a rotation speed of 100-500 rpm for 10-20 minutes, and then dried with air for 1-2 hours to obtain M-SR.

[0007] Preferably, the toughening agent includes one or more of methyl methacrylate-butadiene-styrene copolymer, hydrogenated styrene-butadiene block copolymer, styrene-ethylene-propylene-styrene type block copolymer, emulsion polymerized styrene-butadiene rubber, solution polymerized styrene-butadiene rubber and polybutadiene.

[0008] Preferably, the reactive monomers include one or more of acrylic acid, methacrylic acid, acrylamide, N-hydroxymethyl acrylamide and diethyl dimethacrylate.

[0009] Preferably, the crosslinking agent includes one or more of dibenzoyl peroxide, azo compounds, carbodiimide, dicumyl peroxide and polytriallyl isocyanurate.

[0010] Preferably, the antioxidant includes one or more of diaryl secondary amine, p-phenylenediamine, 2,6-tert-butyl-4-methylphenol, disulfide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0011] Through the above technical scheme, the present application introduces a specific amount of compatibilizer and M-SR into the polylactic acid composite material, which can play a synergistic effect of the two, while maintaining the original excellent performance of polylactic acid, significantly improving the toughness of the polylactic acid composite material, so that it can be more widely used in 3D printing, automobiles, electronics and other fields with high requirements for material toughness. Specifically, the compatibilizer of the present application can effectively improve the interfacial compatibility between polylactic acid and M-SR, reduce the stratification phenomenon of the two, and thus improve the overall mechanical properties of the composite material. The M-SR of the present application is prepared by polymerization reaction of toughening agent, reactive monomer, crosslinking agent and antioxidant, wherein the toughening agent can be effectively dispersed in the polylactic acid matrix to form tiny rubber particles, absorb impact energy and prevent crack propagation; the reactive monomer can further enhance the interaction between M-SR and polylactic acid during the polymerization process, thereby improving the flexibility and durability of the composite material; the crosslinking agent helps to form a stable three-dimensional network structure of toughening agent, reactive monomer and antioxidant, etc., and increase the strength and toughness of the composite material; the antioxidant can effectively alleviate the aging process of the composite material and extend its service life.

[0012] Moreover, the present application forms a stable network structure between toughener, reactive monomer, cross-linking agent and antioxidant by polymerization reaction and then adds it to polylactic acid composite material, which can further improve the various properties of polylactic acid composite material compared to directly melt blending additives such as toughener and antioxidant with polylactic acid. Specifically, after copolymerization of reactive monomers such as toughener and acrylic acid, a copolymer with softness and elasticity can be formed. When this copolymer is added to polylactic acid, the toughness of polylactic acid can be more effectively improved, so that it can better absorb energy when impacted by external force, and reduce the possibility of fracture. And by copolymerization, M-SR can have similar chemical properties with polylactic acid, so as to further improve the compatibility between additives such as toughener, reactive monomer and antioxidant and polylactic acid, so that these components can be evenly dispersed in polylactic acid, reducing the possibility of stratification or peeling. In addition, the M-SR obtained by copolymerization can change the fluidity of polylactic acid, reduce its viscosity, thereby improving its processing performance, making it easier to operate in processing processes such as injection molding and extrusion, and helping to improve production efficiency and product quality.

[0013] Preferably, the compatibilizer is maleic anhydride grafted polyolefin.

[0014] Through the above technical scheme, the present application uses maleic anhydride grafted polyolefin (POE-g-MAH) as a compatibilizer to enhance the interaction between polylactic acid and M-SR, reduce the interface defects between the two, and make M-SR more evenly distributed in the polylactic acid matrix, thereby improving the overall toughness, mechanical strength and thermal stability of the polylactic acid composite material.

[0015] Preferably, the maleic anhydride grafted polyolefin includes one or more of linear low density polyethylene-maleic anhydride copolymer, ethylene-butene-maleic anhydride copolymer, ethylene-octene-maleic anhydride copolymer and polypropylene-maleic anhydride copolymer.

[0016] Preferably, the maleic anhydride grafted polyolefin is prepared by the following method: Dissolve 10-30 parts by weight of polyolefin in xylene and heat to above 120° C., then add 1.4-4.3 parts by weight of maleic anhydride, 0.14-0.43 parts by weight of initiator and 10-20 wt% of crosslinking inhibitor for polyolefin, mix and react for 2-3 hours, stop heating, cool to 60-70° C., add acetone and stir to powder, filter, wash and dry to obtain maleic anhydride grafted polyolefin; The cross-linking inhibitor includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and caprolactam; The initiator and the crosslinking inhibitor are added into the system at the same time.

[0017] Through the above technical scheme, the present application can effectively reduce the occurrence of cross-linking side reactions, improve the melt index, improve fluidity, and make the grafting rate of maleic anhydride grafted polyolefin (POE-g-MAH) at a higher level. Specifically, the present application controls the amount of cross-linking inhibitor, and maintains a higher grafting rate while significantly suppressing the occurrence of side cross-linking reactions, thereby further improving the effect of POE-g-MAH on improving the compatibility between the components in the polylactic acid composite material. In addition, compared to adding the cross-linking inhibitor before the initiator or adding it after the initiator, adding it simultaneously with the initiator can make the melt index and grafting rate both in a better state.

[0018] Preferably, the cross-linking inhibitor is caprolactam; the amount of the cross-linking inhibitor used is 17.5 wt% of the amount of polyethylene used.

[0019] Through the above technical solution, the present application further optimizes the type and amount of the cross-linking inhibitor, further improves the melt index without significantly affecting the grafting rate, and achieves the purpose of inhibiting cross-linking.

[0020] In a second aspect, the present application provides a method for preparing a high-toughness polylactic acid composite material, which adopts the following technical solution: A method for preparing a high-toughness polylactic acid composite material comprises the following steps: S1. Drying polylactic acid, compatibilizer and M-SR by forced air at 60-80°C for 12-24h; S2, the polylactic acid, compatibilizer and M-SR dried in step S1 are mixed and stirred at a rotation speed of 2000-3000 r / min, and then melt-blended and extruded, cooled, pelletized and dried to obtain a high-toughness polylactic acid composite material.

[0021] By adopting the above technical scheme, the preparation method of the present application is simple and easy to operate, and the raw materials are easily available, so it is suitable for large-scale industrial production and has a relatively broad application prospect.

[0022] In summary, this application has the following beneficial technical effects: 1. This application significantly improves the toughness of the polylactic acid composite material by introducing M-SR and a compatibilizer, improves the problem of poor flexibility and brittle fracture of the polylactic acid molecular chain, and makes it suitable for application scenarios with high toughness requirements; 2. The M-SR of the present application is prepared by polymerization of a toughening agent, a reactive monomer, a crosslinking agent and an antioxidant, which ensures its uniform dispersion and high efficiency in the polylactic acid matrix, thereby significantly improving the overall performance of the polylactic acid composite material; 3. The present application optimizes the preparation method of the compatibilizer, so that it has good fluidity while having a good grafting rate, thereby further improving the compatibility of the components in the polylactic acid material by the compatibilizer; 4. The preparation method of the polylactic acid composite material of the present application is simple and easy to operate, and the raw materials are readily available, so it is suitable for large-scale industrial production and has a relatively broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a product picture of pure polylactic acid material; Figure 2 This is a product picture of the high-toughness polylactic acid composite material of the present application. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] In some embodiments of M-SR, the toughening agent includes one or more of methyl methacrylate-butadiene-styrene copolymer (MBS), hydrogenated styrene-butadiene block copolymer (SEBS), styrene-ethylene-propylene-styrene type block copolymer (SEPS), emulsion-polymerized styrene-butadiene rubber (ESBR), solution-polymerized styrene-butadiene rubber (SSBR) and polybutadiene (PB); In some embodiments of M-SR, the reactive monomers include one or more of acrylic acid (AA), methacrylic acid (MAA), acrylamide (AM), N-hydroxymethyl acrylamide, and diethyl dimethacrylate (DMC); In some embodiments of M-SR, the crosslinking agent includes one or more of dibenzoyl peroxide (BPO), azo compounds, carbodiimide, dicumyl peroxide (DCP), and polytriallyl isocyanurate; In some specific embodiments of M-SR, the antioxidant includes one or more of diaryl secondary amines, p-phenylenediamine, 2,6-tert-butyl-4-methylphenol, disulfide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010) and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076).

[0026] In some specific embodiments of M-SR, the above raw materials are used and the following preparation method is followed: 10-20 parts by weight of a toughening agent, 0-20 parts by weight of a reactive monomer, 1-5 parts by weight of a cross-linking agent and 0.1-0.5 parts by weight of an antioxidant are mixed, and the mixture is reacted at a constant temperature of 75-85°C and a pressure of 10-20 MPa for 6-12 hours. After the reaction is completed, the mixture is allowed to stand for 3-6 hours, and then mixed and stirred with ethanol at a speed of 100-500 rpm for 10-20 minutes, and then dried by air for 1-2 hours to obtain M-SR, which is added to a polylactic acid composite material to significantly improve the toughness of the polylactic acid composite material.

[0027] In some embodiments of maleic anhydride grafted polyolefin (POE-g-MAH), the polyolefin comprises one of linear low density polyethylene, ethylene butene copolymer, ethylene octene copolymer and polypropylene; In some embodiments of maleic anhydride grafted polyolefin (POE-g-MAH), the initiator includes one or more of dibenzoyl peroxide (BPO), azo compounds, carbodiimide, dicumyl peroxide (DCP) and polytriallyl isocyanurate; In some embodiments of the maleic anhydride grafted polyolefin (POE-g-MAH), the crosslinking inhibitor includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and caprolactam.

[0028] In some specific embodiments of maleic anhydride grafted polyolefin (POE-g-MAH), the above raw materials are used and the following preparation method is followed: 10-30 parts by weight of polyolefin are dissolved in xylene and heated to above 120°C, then 1.4-4.3 parts by weight of maleic anhydride, 0.14-0.43 parts by weight of initiator and 10-20wt% of cross-linking inhibitor of polyolefin are added and mixed for 2-3h, the initiator and the cross-linking inhibitor are added to the system at the same time, the heating is stopped, acetone is added after cooling to 60-70°C and stirred into powder, filtered, washed and dried to obtain maleic anhydride grafted polyolefin, which is added to the polylactic acid composite material, which can significantly improve the compatibility between polylactic acid and M-SR, thereby further improving the various properties of the polylactic acid composite material.

[0029] In some specific embodiments of the high-toughness polylactic acid composite material, the polylactic acid is one of Type 110, Type 195 and Type 201 produced by Zhejiang Hisun Biomaterials Co., Ltd.

[0030] In some specific embodiments of high-toughness polylactic acid composite materials, the above raw materials are used and the following preparation method is followed: S1, 100 parts by weight of polylactic acid, 5-20 parts by weight of compatibilizer and 5-30 parts of M-SR are blown and dried at a temperature of 60-80°C for 12-24h; S2, the polylactic acid dried in step S1 is first mixed and dispersed at a speed of 100-300r / min, and then the compatibilizer and M-SR prepared above are added and mixed and stirred uniformly at a speed of 2000-3000r / min, and then melt-blended and extruded through a twin-screw extruder, and the temperature of each section of the twin-screw extruder is set as follows: heating zone 1 160-180°C, heating zone 2 170-180°C, heating zone 3 180-300°C, heating zone 4 190-400°C, heating zone 5 200-500°C, heating zone 6 210-500°C, heating zone 7 220-800°C, heating zone 8 230-800°C, heating zone 9 240-800°C, heating zone 10 250-1100°C, heating zone 11 260-1100°C, heating zone 12 270-1100°C, heating zone 13 280-1300°C, heating zone 14 290-1500°C, heating zone 15 The temperature of hot zone 3 is 180-200℃, heating zone 4 is 180-200℃, heating zone 5 is 185-200℃, heating zone 6 is 185-200℃, heating zone 7 is 190-210℃, and the die head temperature is 180-200℃. The main engine speed of the twin-screw extruder is 120-240rpm, the screw aspect ratio is 40-48:1, circulating cold water cooling, pelletizing, feeding speed is 10-30rpm, cutting speed is 5-10rpm, and vacuum drying is carried out at a temperature of 60-80℃ for 12-24h. The obtained high-toughness polylactic acid composite material has high notched impact strength and good toughness, and can be widely used in 3D printing, automobiles, electronics and other fields with high requirements on material toughness.

[0031] Based on the above content, the present application further adopts the following examples and comparative examples to demonstrate the influence of the selection and dosage of raw materials of the present application on the changes of various properties of polylactic acid.

[0032] Unless otherwise specified, the raw materials used in this application are all commercially available products.

[0033] The methyl methacrylate-butadiene-styrene copolymer (MBS) of the present application has a CAS number of 25053-09-2 and a molecular weight of 258.36.

[0034] The pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010) of the present application has a CAS number of 6683-19-8 and an effective substance content of 98%.

[0035] The linear low-density polyethylene (LLDPE) of this application has a density of 0.924 g / cm 3 , melt flow rate is 3.6g / 10min, Shore hardness is 53D, tensile modulus is 225MPa, tensile strength is 11.0MPa, elongation at break is 14%, and melting temperature is 121°C.

[0036] Preparation Example 1.1 The preparation method of M-SR comprises the following steps: 100 kg of toughening agent (methyl methacrylate-butadiene-styrene copolymer), 200 kg of reaction monomer (methacrylic acid), 10 kg of cross-linking agent (diisopropylbenzene peroxide) and 5 kg of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed and put into a high-pressure reactor. The mixture was reacted at a constant temperature of 75°C and a pressure of 20 MPa for 6 hours. After the reaction was completed, the mixture was allowed to stand for 6 hours, and then mixed and stirred with ethanol at a speed of 100 rpm for 20 minutes, and then dried with air for 1 hour to obtain M-SR.

[0037] Preparation Example 1.2 The preparation method of M-SR comprises the following steps: 200 kg of toughening agent (methyl methacrylate-butadiene-styrene copolymer), 50 kg of cross-linking agent (diisopropyl peroxide) and 1 kg of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) were mixed and placed in a high-pressure reactor. The mixture was reacted at a constant temperature of 85°C and a pressure of 10 MPa for 12 hours. After the reaction was completed, the mixture was allowed to stand for 3 hours, and then mixed and stirred with ethanol at a speed of 500 rpm / min for 10 minutes, and then dried with air for 2 hours to obtain M-SR.

[0038] Preparation Example 2.1.1 The preparation method of maleic anhydride grafted polyolefin comprises the following steps: 10 kg of polyolefin (linear low-density polyethylene) was dissolved in 60 L of xylene and heated to 120°C. After the linear low-density polyethylene was dissolved, 1.4 kg of maleic anhydride was added, followed by 0.14 kg of initiator (diisopropylbenzene peroxide) and 1 kg of cross-linking inhibitor (caprolactam) and mixed for 2 hours. The heating was stopped, and after cooling to 60°C, acetone was added and stirred into powder. The powder was filtered, washed and dried to obtain maleic anhydride grafted polyolefin.

[0039] Preparation Example 2.1.2 The preparation method of maleic anhydride grafted polyolefin comprises the following steps: 20 kg of polyolefin (linear low-density polyethylene) was dissolved in 120 L of xylene and heated to 122 ° C. After the linear low-density polyethylene was dissolved, 3 kg of maleic anhydride was added, followed by 0.3 kg of initiator (diisopropylbenzene peroxide) and 2 kg of cross-linking inhibitor (caprolactam) and mixed for 2.5 hours, then the heating was stopped, and after cooling to 65 ° C, acetone was added and stirred into powder, filtered, washed and dried to obtain maleic anhydride grafted polyolefin.

[0040] Preparation Example 2.1.3 The preparation method of maleic anhydride grafted polyolefin comprises the following steps: 30 kg of polyolefin (linear low-density polyethylene) was dissolved in 180 L of xylene and heated to 125 ° C. After the linear low-density polyethylene was dissolved, 4.3 kg of maleic anhydride was added, followed by 0.43 kg of initiator (diisopropylbenzene peroxide) and 3 kg of cross-linking inhibitor (caprolactam) and mixed for 3 hours, then the heating was stopped, and after cooling to 70 ° C, acetone was added and stirred into powder, filtered, washed and dried to obtain maleic anhydride grafted polyolefin.

[0041] Preparation Example 2.2.1 The difference from Preparation Example 1.1.2 is that an equal amount of caprolactam is replaced by N,N-dimethylformamide, and the rest is the same as Preparation Example 1.1.2.

[0042] Preparation Example 2.2.2 The difference from Preparation Example 1.1.2 is that an equal amount of caprolactam is replaced by N,N-dimethylacetamide, and the rest is the same as Preparation Example 1.1.2.

[0043] Preparation Example 2.2.3 The difference from Preparation Example 1.1.2 is that an equal amount of caprolactam is replaced by dimethyl sulfoxide, and the rest is the same as Preparation Example 1.1.2.

[0044] Preparation Example 2.3.1 The difference from Preparation Example 1.1.2 is that the amount of caprolactam used is 17.5wt% of the amount of linear low-density polyethylene, that is, the amount of caprolactam used is 3.5kg, and the rest is the same as Preparation Example 1.1.2.

[0045] Preparation Example 2.3.2 The difference from Preparation Example 1.1.2 is that the amount of caprolactam used is 20wt% of the amount of linear low-density polyethylene, that is, the amount of caprolactam used is 4kg, and the rest is the same as Preparation Example 1.1.2.

[0046] Preparation Example 2.3.3 The difference from Preparation Example 1.1.2 is that the amount of caprolactam used is 5wt% of the amount of linear low-density polyethylene, that is, the amount of caprolactam used is 1kg, and the rest is the same as Preparation Example 1.1.2.

[0047] Preparation Example 2.3.4 The difference from Preparation Example 1.1.2 is that the amount of caprolactam used is 30wt% of the amount of linear low-density polyethylene, that is, the amount of caprolactam used is 6kg, and the rest is the same as Preparation Example 1.1.2.

[0048] Preparation Example 2.4.1 The difference from Preparation Example 1.1.2 is that caprolactam is added 20 minutes before dicumyl peroxide, and the rest is the same as Preparation Example 1.1.2.

[0049] Preparation Example 2.4.2 The difference from Preparation Example 1.1.2 is that caprolactam is added 20 minutes after dicumyl peroxide, and the rest is the same as Preparation Example 1.1.2.

[0050] The maleic anhydride grafted polyolefin prepared in the above preparation examples 2.1.1-2.4.2 was subjected to melt index and grafting rate measurement, wherein the melt index was measured on a XRZ-400 melt index meter, the capillary diameter was 2 mm, the aspect ratio (L / D) was 10:1, and the melt index measurement conditions were a temperature of 140°C and a load of 2160 g. The grafting rate was measured by Fourier transform infrared spectroscopy with characteristic peaks and calculated according to the Lambert-Beer law, and the results are shown in Table 1.

[0051] Table 1 Maleic anhydride grafted polyolefin measurement results project Melt index (g / min) Grafting rate (%) Preparation Example 2.1.1 1.52 2.33 Preparation Example 2.1.2 1.55 2.28 Preparation Example 2.1.3 1.53 2.31 Preparation Example 2.2.1 1.42 1.59 Preparation Example 2.2.2 1.65 1.65 Preparation Example 2.2.3 1.59 1.42 Preparation Example 2.3.1 2.84 1.86 Preparation Example 2.3.2 3.01 1.68 Preparation Example 2.3.3 0.61 2.52 Preparation Example 2.3.4 3.48 1.59 Preparation Example 2.4.1 1.39 1.48 Preparation Example 2.4.2 0.78 2.31 As can be seen from Table 1, the maleic anhydride grafted polyolefins prepared in Preparation Examples 2.1.1-2.1.3 have good fluidity and a high grafting rate. The difference between Preparation Examples 2.2.1-2.2.3 and Preparation Example 2.1.2 is that caprolactam is replaced with other crosslinking inhibitors. As can be seen from Table 1, although some crosslinking inhibitors can slightly increase the melt index of maleic anhydride grafted polyolefins, they all significantly reduce the grafting rate of maleic anhydride grafted polyolefins. It can be seen that further using caprolactam as a crosslinking inhibitor can inhibit the occurrence of crosslinking side reactions while ensuring a high grafting rate.

[0052] The difference between Preparation Examples 2.3.1-2.3.4 and Preparation Example 2.1.2 lies in the different amounts of caprolactam used. As can be seen from Table 1, when the amount of caprolactam is further optimized to 17.5 wt% of the linear low-density polyethylene, although the grafting rate is reduced, the increase in the melt index is much greater than the decrease in the grafting rate, and both the grafting rate and the melt index have reached a relatively satisfactory state.

[0053] The difference between Preparation Example 2.4.1-2.4.2 and Preparation Example 2.1.2 is that the order of adding the crosslinking inhibitor and the initiator is different. As can be seen from Table 1, the melt index and grafting rate of Preparation Examples 2.4.1-2.4.2 are both lower than those of Preparation Example 2.1.2. It can be seen that adding the crosslinking inhibitor and the initiator at the same time can inhibit the occurrence of crosslinking side reactions while ensuring a higher grafting rate.

[0054] Example 1.1.1 A method for preparing a high-toughness polylactic acid composite material comprises the following steps: S1. Dry 100 kg of polylactic acid (type 110), 5 kg of the compatibilizer prepared in Preparation Example 2.1.1 and 30 kg of the M-SR prepared in Preparation Example 1.1 at 60°C for 24 h; S2. The polylactic acid dried in step S1 is first mixed and dispersed at a speed of 100 r / min, and then a compatibilizer and M-SR are added and mixed and stirred at a speed of 3000 r / min. After that, the mixture is melt-blended and extruded through a twin-screw extruder. The temperature of each section of the twin-screw extruder is set as follows: heating zone 160-180°C, heating zone 2 170-180°C, heating zone 3 180-200°C, heating zone 4 180-200°C, heating zone 5 185-200°C, heating zone 6 185-200°C, heating zone 7 190-210°C, and die head temperature 180-200°C. The main engine speed of the twin-screw extruder is 120 rpm, the screw aspect ratio is 48:1, circulating cold water cooling, pelletizing, the feeding speed is 10 rpm, the cutting speed is 10 rpm, and vacuum drying is performed at a temperature of 60°C for 24 hours to obtain a polylactic acid composite material.

[0055] Example 1.1.2 A method for preparing a high-toughness polylactic acid composite material comprises the following steps: S1, 100 kg of polylactic acid (type 110), 10 kg of the compatibilizer prepared in Preparation Example 2.1.2 and 5 kg of the M-SR prepared in Preparation Example 1.2 were dried by forced air at 80°C for 12 h; S2, the polylactic acid dried in step S1 is first mixed and dispersed at a speed of 300r / min, and then a compatibilizer and M-SR are added and mixed and stirred at a speed of 2000r / min, and then melt-blended and extruded through a twin-screw extruder, and the temperature of each section of the twin-screw extruder is set as follows: heating zone 160-180°C, heating zone 2 170-180°C, heating zone 3 180-200°C, heating zone 4 180-200°C, heating zone 5 185-200°C, heating zone 6 185-200°C, heating zone 7 190-210°C, die head temperature 180-200°C, the main engine speed of the twin-screw extruder is 240rpm, the screw aspect ratio is 40:1, circulating cold water cooling, pelletizing, feeding speed is 30rpm, cutting speed is 5rpm, and vacuum drying is performed at a temperature of 80°C for 12h to obtain a polylactic acid composite material.

[0056] Example 1.1.3 A method for preparing a high-toughness polylactic acid composite material comprises the following steps: S1. Dry 100 kg of polylactic acid (type 110), 20 kg of the compatibilizer prepared in Preparation Example 2.1.3 and 20 kg of the M-SR prepared in Preparation Example 1.2 at 70°C for 18 h; S2, the polylactic acid dried in step S1 is first mixed and dispersed at a speed of 200r / min, and then a compatibilizer and M-SR are added and mixed and stirred at a speed of 2500r / min, and then melt-blended and extruded through a twin-screw extruder, and the temperature of each section of the twin-screw extruder is set as follows: heating zone 160-180°C, heating zone 2 170-180°C, heating zone 3 180-200°C, heating zone 4 180-200°C, heating zone 5 185-200°C, heating zone 6 185-200°C, heating zone 7 190-210°C, die head temperature 180-200°C, the main engine speed of the twin-screw extruder is 180rpm, the screw aspect ratio is 44:1, circulating cold water cooling, pelletizing, feeding speed is 20rpm, cutting speed is 8rpm, and vacuum drying is performed at a temperature of 70°C for 18h to obtain a polylactic acid composite material.

[0057] Example 1.2.1 The difference from Example 1.1.2 is that in step S1, the amount of M-SR used is 10 kg, and the rest is the same as Example 1.1.2.

[0058] Example 1.2.2 The difference from Example 1.1.2 is that in step S1, the amount of M-SR used is 20 kg, and the rest is the same as Example 1.1.2.

[0059] Example 1.2.3 The difference from Example 1.1.2 is that in step S1, the amount of M-SR used is 30 kg, and the rest is the same as Example 1.1.2.

[0060] Example 2.1 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.2.1, and the rest is the same as Example 1.1.2.

[0061] Example 2.2 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.2.2, and the rest is the same as Example 1.1.2.

[0062] Example 2.3 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.2.3, and the rest is the same as Example 1.1.2.

[0063] Example 2.4 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.3.1, and the rest is the same as Example 1.1.2.

[0064] Example 2.5 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.3.2, and the rest is the same as Example 1.1.2.

[0065] Example 2.6 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.3.3, and the rest is the same as Example 1.1.2.

[0066] Example 2.7 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.3.4, and the rest is the same as Example 1.1.2.

[0067] Example 2.8 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.4.1, and the rest is the same as Example 1.1.2.

[0068] Example 2.9 The difference from Example 1.1.2 is that the maleic anhydride grafted polyolefin prepared in Preparation Example 2.1.2 in step S1 is replaced by the maleic anhydride grafted polyolefin prepared in Preparation Example 2.4.2, and the rest is the same as Example 1.1.2.

[0069] Comparative Example 1.1 The difference from Example 1.1.2 is that no compatibilizer is added in step S1, and the rest is the same as Example 1.1.2.

[0070] Comparative Example 1.2 The difference from Example 1.1.2 is that M-SR is not added in step S1, and the rest is the same as Example 1.1.2.

[0071] Comparative Example 2.1 The difference from Example 1.1.2 is that 200 kg of toughening agent (methyl methacrylate-butadiene-styrene copolymer) and 1 kg of antioxidant are directly melt-blended with polylactic acid and extruded, and the rest is the same as Example 1.1.2.

[0072] Comparative Example 3.1 The difference from Example 1.1.2 is that the amount of M-SR used is 4 kg, and the rest is the same as Example 1.1.2.

[0073] Comparative Example 3.2 The difference from Example 1.1.2 is that the amount of M-SR used is 35 kg, and the rest is the same as Example 1.1.2.

[0074] Performance Testing The polylactic acid composite materials obtained in the above embodiments and comparative examples were tested for relevant properties, and the results are shown in Table 2. The relevant performance tests mainly include tensile strength, elongation at break, notched impact strength, flexural strength and flexural modulus, wherein the tensile strength is measured by referring to the method in GB / T 1040, and the stretching speed is 50 mm / min; the elongation at break is measured by referring to the method in DB / T1040, and the stretching speed is 50 mm / min; the notched impact strength is measured by referring to the method in GB / T 1843, and the energy is 5.5 J and the speed is 3.5 m / s; the flexural strength is measured by referring to the method in GB / T 9341, and the speed is 2 mm / min; the flexural modulus is measured by referring to the method in GB / T 9341, and the speed is 2 mm / min.

[0075] Table 2 Performance test results As can be seen from Table 2, the high-toughness polylactic acid composite material obtained in Examples 1.1.1-1.2.3 of the present application has a tensile strength of not less than 36.57 MPa, an elongation at break of not less than 12.16%, and a notched impact strength of not less than 9.18 KJ / m 2 , the highest can reach 37.28KJ / m 2 The flexural strength is not less than 53.55 MPa, and the flexural modulus is not less than 1918.46 MPa. It can be seen that the high-toughness polylactic acid composite material prepared in this application has high toughness and good strength. All performances are maintained at a good level. The product quality is high and can be widely used in 3D printing, automobiles, electronics and other fields.

[0076] The difference between Examples 2.1-2.9 and Example 1.1.2 is that the preparation methods of maleic anhydride grafted polyolefin are different. As can be seen from Table 2, the strength and toughness of Examples 2.1-2.3 are lower than those of Example 1.1.2, which indicates that the maleic anhydride grafted polyolefin obtained by using caprolactam as a crosslinking inhibitor can more fully improve the compatibility between polylactic acid and M-SR due to its higher grafting rate and fluidity, thereby improving the overall performance of the polylactic acid composite material. The toughness of Example 2.4 is slightly higher than that of Example 1.1.2, which indicates that when the amount of caprolactam is further optimized to 17.5wt% of the amount of linear low-density polyethylene, the improvement effect of maleic anhydride grafted polyolefin on the compatibility of polylactic acid and M-SR can be further improved, thereby improving the overall performance of the polylactic acid composite material. The strength and toughness of Examples 2.6-2.7 are lower than those of Example 1.1.2, which indicates that too low or too high a dosage of caprolactam will reduce the improvement effect of maleic anhydride grafted polyolefin on the compatibility of polylactic acid and M-SR, thereby reducing the overall performance of the polylactic acid composite material. The strength and toughness of Examples 2.8-2.9 are lower than those of Example 1.1.2, which indicates that if caprolactam is not added simultaneously with the crosslinking agent, the improvement effect of maleic anhydride grafted polyolefin on the compatibility of polylactic acid and M-SR will be reduced, thereby reducing the overall performance of the polylactic acid composite material.

[0077] The difference between Comparative Example 1.1 and Example 1.1.2 is that no compatibilizer is added. As can be seen from Table 2, the strength and toughness of Comparative Example 1.1 are lower than those of Example 1.1.2, which indicates that the addition of the compatibilizer can significantly improve the compatibility between polylactic acid and M-SR, thereby improving the toughening effect of M-SR on the polylactic acid composite material. At the same time, the better compatibility also makes the composite material have good strength, and the resulting product is of higher quality.

[0078] The difference between Comparative Example 1.2 and Example 1.1.2 is that M-SR is not added. As can be seen from Table 2, the toughness of Comparative Example 1.2 is significantly lower than that of Example 1.1.2, which indicates that the addition of M-SR can have a good toughening effect on the polylactic acid composite material, thereby improving the toughness of the polylactic acid composite material.

[0079] The difference between Comparative Example 2.1 and Example 1.1.2 is that the toughening agent and antioxidant are directly melt-blended with polylactic acid. As can be seen from Table 2, the strength and toughness of Comparative Example 2.1 are lower than those of Example 1.1.2. This shows that compared with directly melt-blending the toughening agent and other additives with polylactic acid, the present application first cross-links the toughening agent and reactive monomers, antioxidants, etc. and then adds them to the polylactic acid composite material, which can further enhance the compatibility between polylactic acid and the toughening agent, and further enhance the modification effect of the toughening agent and other additives on the polylactic acid composite material, thereby further improving the various properties of the polylactic acid composite material.

[0080] The difference between Comparative Examples 3.1-3.2 and Example 1.1.2 is that the amount of M-SR used is not within the scope of the present application. As can be seen from Table 2, the toughness of Comparative Example 3.1 is significantly lower than that of Example 1.1.2, and the strength of Comparative Example 3.2 is significantly lower than that of Example 1.1.2. This shows that if the amount of M-SR used is too low, its reinforcing effect on the polylactic acid composite material cannot be fully exerted, but if the amount is too high, the polylactic acid composite material will not be able to maintain a better strength.

[0081] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high-toughness polylactic acid composite material, characterized in that: The raw materials used include the following components: 100 parts by weight of polylactic acid; Compatibilizer 5-20 parts by weight; M-SR 5-30 parts by weight; The M-SR is prepared by polymerization of a toughening agent, a reactive monomer, a crosslinking agent and an antioxidant.

2. A high-toughness polylactic acid composite material according to claim 1, characterized in that: The M-SR is prepared by the following method: 10-20 parts by weight of toughening agent, 0-20 parts by weight of reactive monomer, 1-5 parts by weight of cross-linking agent and 0.1-0.5 parts by weight of antioxidant are mixed, and the mixture is reacted at a temperature of 75-85°C and a pressure of 10-20 MPa for 6-12 hours. After the reaction is completed, the mixture is allowed to stand for 3-6 hours, and then mixed and stirred with ethanol at a rotation speed of 100-500 rpm for 10-20 minutes, and then dried with air for 1-2 hours to obtain M-SR.

3. A high-toughness polylactic acid composite material according to claim 2, characterized in that: The toughening agent includes one or more of methyl methacrylate-butadiene-styrene copolymer, hydrogenated styrene-butadiene block copolymer, styrene-ethylene-propylene-styrene type block copolymer, emulsion polymerized styrene-butadiene rubber, solution polymerized styrene-butadiene rubber and polybutadiene.

4. The high-toughness polylactic acid composite material according to claim 2, characterized in that: The reactive monomers include one or more of acrylic acid, methacrylic acid, acrylamide, N-hydroxymethyl acrylamide and diethyl dimethacrylate.

5. The high-toughness polylactic acid composite material according to claim 2, characterized in that: The crosslinking agent includes one or more of dibenzoyl peroxide, azo compounds, carbodiimide, dicumyl peroxide and polytriallyl isocyanurate.

6. The high-toughness polylactic acid composite material according to claim 2, characterized in that: The antioxidant includes one or more of diaryl secondary amine, p-phenylenediamine, 2,6-tert-butyl-4-methylphenol, disulfide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

7. The high-toughness polylactic acid composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyolefin.

8. The high-toughness polylactic acid composite material according to claim 7, characterized in that: The maleic anhydride grafted polyolefin is prepared by the following method: Dissolve 10-30 parts by weight of polyolefin in xylene and heat to above 120° C., then add 1.4-4.3 parts by weight of maleic anhydride, 0.14-0.43 parts by weight of initiator and 10-20 wt% of crosslinking inhibitor for polyolefin, mix and react for 2-3 hours, stop heating, cool to 60-70° C., add acetone and stir to powder, filter, wash and dry to obtain maleic anhydride grafted polyolefin; The cross-linking inhibitor includes one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and caprolactam; The initiator and the crosslinking inhibitor are added into the system at the same time.

9. The high-toughness polylactic acid composite material according to claim 8, characterized in that: The cross-linking inhibitor is caprolactam; the amount of the cross-linking inhibitor used is 17.5wt% of the amount of polyethylene used.

10. A method for preparing the high-toughness polylactic acid composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Drying polylactic acid, compatibilizer and M-SR by forced air at 60-80°C for 12-24h; S2, the polylactic acid, compatibilizer and M-SR dried in step S1 are mixed and stirred at a rotation speed of 2000-3000 r / min, and then melt-blended and extruded, cooled, pelletized and dried to obtain a high-toughness polylactic acid composite material.

Citation Information

Patent Citations

  • Silane-coupling-agent-modified polylactic acid 3D printing wire rod and manufacturing method thereof

    CN106221152A

  • PLA / TPU double-component wire for 3D printing and preparation method thereof

    CN111890650A